Changes of bone mineral density after cementless total hip arthroplasty with two different stems - Sano, Keiji (Springer-Verlag, 2007)
Cementless total hip arthroplasty has achieved reliable long-term results since porous coatings were developed, but postoperative changes around the stem remain poorly documented. In this study, changes of the bone mineral density (BMD) were compared between two types of cementless stem. In group B (28 patients with 31 hips), a straight tapered stem with porous plasma spray coating on the proximal 1/4 was used, while group S (24 patients with 26 hips) was given a fluted, tri-slot stem with porous hydroxyapatite coating on the proximal 1/3. In group B, there was an early decrease of BMD, which recovered after 12 months, indicating that stress shielding was minimal. In group S, however, BMD continued to decrease without recovery. The stem shape and radiological findings suggested that the cause of stress shielding in group S was distal fixation.